The Influence of Landscape Patterns on the Bird Diversity of Four Urban Parks - Bonança, Renan Augusto; Dunning, John B. Barney; da Silva, Alexandre Marco [UNESP] (Wiley, 2017)
In our study, we aimed to investigate the influence of landscape patterns on the diversity of birds in four urban parks. The parks are located in a region that has a high value of regional biodiversity and is also highly urbanized (Jundiai, state of São Paulo [SP], in Southeastern Brazil). Using a set of aerial photos, the surrounding landscape was divided into two regions (rings) and corresponding landscape metrics were calculated. The presence of bird species was recorded monthly over a one-year period and classified according to selected ecological criteria. The land cover of the areas surrounding each park was primarily buildings and residences. Bird diversity was significantly correlated with the presence/proximity of water bodies. We state that the potential of the parks to harbor bird species is not negligible. Managing the area surrounding a park to increase the percentage of forested area and the size of forest fragments is as crucial as managing the core park area, especially for improving its attractiveness for new bird species.